Progesterone, selected heavy metals and micronutrients in pregnant Nigerian women with a history of recurrent spontaneous abortion (2012)
Background: Environmental and endocrine factors have been implicated in the aetiology of recurrent abortion, with poorly understood roles. Luteal phase insufficiency marked with insufficient progesterone secretion has been reported. Objective: To define the involvement of progesterone, trace metals, and Vitamin E in pregnant women with history of recurrent spontaneous abortion. Methods: Convenience sampling method was used to recruit 69 pregnant women aged 21-41 years with gestational age of 0-20 weeks in this case-control study. Thirty five (cases) and thirty four (controls) had previous and no history of recurrent spontaneous abortion respectively. Demographic characteristics and 10mls of blood samples were obtained from each subject. Serum obtained was used for the determination of progesterone, zinc, copper, selenium, iron, magnesium, manganese, chromium, lead, cadmium, and serum vitamin E by standard methods. Results: Results showed statistically significant decreases (p<0.05) in the serum zinc, copper, and vitamin E and a significant elevation (p<0.05) in the serum selenium, lead, and cadmium in cases compared with controls. Insignificant decrease (p=0.07) was observed in the serum progesterone when cases were compared with controls. Conclusion: Results suggest that elevated serum heavy metals (cadmium and lead) and reduction of essential micronutrients (zinc, copper and vitamin E) may contribute to recurrent spontaneous abortion.